Medical therapies for postoperative Crohn's disease. (February 2021) - Shah, Ravi S.; Click, Benjamin H.
Postoperative recurrence of Crohn's disease is common and requires a multidisciplinary approach between surgeons and gastroenterologists in the perioperative and postoperative period to improve outcomes in this patient population. Endoscopic recurrence precedes clinical and surgical recurrence and endoscopic monitoring is crucial to guide postoperative management. Risk stratification of patients is recommended to guide early prophylactic management, and follow-up endoscopic monitoring can guide intensification of therapy. This review summarizes evidence behind postoperative recurrence rates, disease monitoring techniques, nonbiologic and biologic therapies available to prevent and treat postoperative recurrence, risk factors associated with recurrence, and postoperative management strategies guided by endoscopic monitoring.